Characteristics of Peat with Different Depths in Supporting Growth and Productivity of Oil Palm - Ida Nur Santi; Hayata Hayata; Bangun Bangun (UNIVERSITY OF LAMPUNG, 2023)
The potential for oil palm production on peatlands is very diverse; different types of peat, maturity, and depth significantly influence yields. This study aims to determine the characteristics of peat with different depths in supporting the growth and productivity of oil palm. The research was conducted at the PT Kaswari Unggul Palm Oil Plantation in Jambi Province using laboratory surveys and test methods. Observations done were Plant height, Number of Fresh Fruit Bunches (FFB), Stem Circumference, FFB Weight, Midrib Length, Palm Oil Productivity, Light Intensity. Soil analysis were available-P, total-Fe-, total N, organic-C and CEC, pH, Al-exchange, total-K, Soil Moisture, and Peat Maturity. In shallow peat, the soil is more completely decomposed and provides nutrients that can be absorbed by plants so that plants grow better. The results showed that the shallow peat has a maturity level of sapric peat (very ripe) and peat in hemic maturity (slightly mature). Also, the depth of peat will affect the value of total-N, pH, available-P, and K-exchange and does not affect organic-C, total-Fe, CEC, and Al-exchange. Moreover, the growth and production of oil palm on shallow peat were better than on deep peat.